2018
DOI: 10.1016/j.rmed.2018.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Role of IL-15 in interstitial lung diseases in amyopathic dermatomyositis with anti-MDA-5 antibody

Abstract: IL-15, as well as IL-10, may play a key role in the progression of the patients with ADM-ILD with anti-MDA-5 antibody positive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 35 publications
2
8
0
1
Order By: Relevance
“…Thus, IL-15 production is also potentially involved in immune responses such as the activation of macrophages and NK cells as well as the function of other biomarkers in patients with PM/DM-RPILD. In line with our findings, nonsurvivors with anti-MDA5 antibodypositive ILD exhibit higher serum IL-15 levels before treatment compared with survivors with anti-MDA5 antibody-positive ILD [29]. Accordingly, these previous reports and the present study support that serum IL-15 is a useful biomarker for predicting the prognosis of patients with PM/DM-RPILD.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, IL-15 production is also potentially involved in immune responses such as the activation of macrophages and NK cells as well as the function of other biomarkers in patients with PM/DM-RPILD. In line with our findings, nonsurvivors with anti-MDA5 antibodypositive ILD exhibit higher serum IL-15 levels before treatment compared with survivors with anti-MDA5 antibody-positive ILD [29]. Accordingly, these previous reports and the present study support that serum IL-15 is a useful biomarker for predicting the prognosis of patients with PM/DM-RPILD.…”
Section: Discussionsupporting
confidence: 92%
“…We believe that aggressive treatment with immunosuppressants might lead to CMV infections. It has been reported that IL-15 was significantly elevated in non-survivors, most of whom had CMV antigenemia [32]. IL-15 is a proinflammatory cytokine, secreted mainly by mononuclear cells following viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is consistent with the poor survival documented in patients with interstitial lung disease associated with clinically amyopathic dermatomyositis who are antimelanoma differentiation-associated gene 5 antibody positive and show an increase in serum IL-10 during their clinical course. 49 …”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is consistent with the poor survival documented in patients with interstitial lung disease associated with clinically amyopathic dermatomyositis who are antimelanoma differentiation-associated gene 5 antibody positive and show an increase in serum IL-10 during their clinical course. 49 The results of this study could alter the treatment strategy for AE-IIPs. Nintedanib 50 is known to suppress the effects of profibrotic cytokines, including VEGF, 51 b-FGF 52 and PDGF.…”
Section: Open Accessmentioning
confidence: 93%